The Clientʼs Interest Protection as the Added Value of Bank Management, According to the Concept of Corporate Social Responsibility - Wierzbicka, Beata; Lechicka-Kostuch, Maria (Journal of Finance and Financial Law, 2016)
Demanding, well informed, fickle and impatient customer of the bank is a major challenge for the organization. Creating a package of benefits that guarantee a lasting relationship between the customer and the bank, forces a new approach to the concept of managing these relationships. The aim of the article is to indicate the possibility of using the pro-consumer and pro-social bank activities to implement innovations in the service process, the source of which can become clients of the bank. Costumerʼs creativity and the social responsibility of the bank can transfer to increased customer satisfaction due to his requirements satisfaction set in relation to the service provided by the bank.